2020
DOI: 10.1016/j.ausmj.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

How to Grow the Sharing Economy? Create Prosumers!

Abstract: The sharing economy has changed many rules of business. One of those rules is the role of the firm and – importantly – the role of consumers, who can perform two roles and become both providers and consumers, i.e. “prosumers”. Therefore, the key network effect to leveraging the power of the sharing economy is for one-sided users, those who are consumers (e.g., Airbnb guests) or providers (e.g., Airbnb hosts), to add the second role and perform as providers and consumers and become prosumers (e.g., those who ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 86 publications
(147 reference statements)
1
38
0
1
Order By: Relevance
“…Here, up to 80% of respondents put clear statement that rating (obtained by customers) play a significant role in the sharing economy. Also other studies confirmed this fact [7,11].…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…Here, up to 80% of respondents put clear statement that rating (obtained by customers) play a significant role in the sharing economy. Also other studies confirmed this fact [7,11].…”
Section: Resultssupporting
confidence: 59%
“…It means when one is experiencing good trustworthy service, and this service is overcoming ones' expectations person can feel gratitude. Consumers who experienced such a service are more willing to adopt the role of the provider in the sharing economy in the future [7]. Nadeen [11] confirmed, that being cared and understood -(multidimensional social support), has strong impact to value co-creation trough sharing economy platforms.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations